2008
DOI: 10.1007/s00467-008-0934-7
|View full text |Cite
|
Sign up to set email alerts
|

The R229Q mutation in NPHS2 may predispose to proteinuria in thin-basement-membrane nephropathy

Abstract: Thin-basement-membrane nephropathy (TBMN) is characterized by persistent dysmorphic hematuria, and the presence of proteinuria is a risk factor for renal impairment. TBMN is often due to mutations in the COL4A3 and COL4A4 genes, and this study determined whether additional mutations in genes encoding other structures in the glomerular filtration barrier contributed to the development of proteinuria. Fifty-six unrelated individuals with TBMN including 18 (32%) with proteinuria > or = 300 mg/L and ten (18%) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 30 publications
2
33
1
4
Order By: Relevance
“…Extended founder effects found in Cyprus for 2 mutations in the COL4A3 gene can greatly help in identifying modifier variants due to less prominent genetic background ‘noise'. Previously published data [17,18] encouraged us to proceed in direct re-sequencing of the entire coding region of the NPHS2 gene in ‘severe' patients, with the hope to identify more candidate modifier variants. We found 7 patients with severe phenotype that carried variant p.Arg229Gln or p.Glu237Gln, while none of the mildly affected patients had inherited any non-synonymous variant of obvious significance (p = 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extended founder effects found in Cyprus for 2 mutations in the COL4A3 gene can greatly help in identifying modifier variants due to less prominent genetic background ‘noise'. Previously published data [17,18] encouraged us to proceed in direct re-sequencing of the entire coding region of the NPHS2 gene in ‘severe' patients, with the hope to identify more candidate modifier variants. We found 7 patients with severe phenotype that carried variant p.Arg229Gln or p.Glu237Gln, while none of the mildly affected patients had inherited any non-synonymous variant of obvious significance (p = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Two different studies have demonstrated that variant p.Arg229Gln in podocin, encoded by the NPHS2 gene, predisposes TBMN patients to proteinuria and renal failure [17,18]. Pathogenic podocin mutations are responsible for the steroid-resistant nephrotic syndrome (SRNS-OMIM: 600995), which follows the autosomal recessive mode of inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the implication that variant R229Q in the podocin protein may predispose to proteinuria in TBMN [12] is somewhat premature and needs further experimentation. It is equally important either to confirm this association or to reject it; however, it is of paramount importance for us to identify the factor or factors that clearly predispose a subgroup of TBMN patients to proteinuria, or even FSGS and renal failure, thereby enabling us to identify high-risk patients for early intervention.…”
mentioning
confidence: 97%
“…In a recent publication in this journal Tonna et al [12] reported on 56 TBMN patients (on the basis of persistent hematuria), some of whom also had proteinuria of ≥300 mg/l, or ≥500 mg/l. Among these, 3 of 5 (60%) who carried the R229Q variant of the glomerular filtration barrier protein podocin [encoded by the nephrosis 2 (NPHS2) gene] had proteinuria of ≥500 mg/l, whereas only 7 of 51 (14%) who did not carry R229Q had a similar level of proteinuria.…”
mentioning
confidence: 99%
“…The patient's mother had negative urine findings with the same mutation of COL4A4. The different phenotype of the same mutation may be explained by the involvement of chemical mediators or other structural proteins, such as the glomerular podocyte, which may interact with type IV collagen [6,7]. Our patient's phenomena that he showed mild to nephrotic-range proteinuria only in various episodes of acute infection may suggest the involvement of chemical mediators such as cytokine or chemokine.…”
Section: Case Reportmentioning
confidence: 75%